Kualitas Pelayanan Administrasi Kependudukan dalam Peningkatan Pelayanan Publik - Nufaris Elisa (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Population administration services constitute one of the main pillars of public service delivery in Indonesia. The quality of these services directly affects the fulfillment of citizens' civil rights and their access to other public services, such as healthcare, education, and social assistance. This study aims to analyze the quality of population administration services, identify the factors that hinder service delivery, and formulate strategies for improvement. A descriptive qualitative approach was employed, with data collected through a literature review, observations, and in-depth interviews. The findings indicate that improvements in service quality are strongly influenced by the utilization of information technology (e-Government), the competence of Civil Servants (Aparatur Sipil Negara/ASN), the enhancement of facilities and infrastructure, and the transparency of service standards. The main challenges identified include technical network constraints, varying levels of digital literacy among the public, and resistance to changes in service systems. The study concludes that citizen-centered digital transformation is a key factor in creating public services that are responsive, transparent, and accountable. Population administration services are also recognized as a fundamental right of citizens and serve as an important indicator of the effectiveness of public service delivery by local governments. This study further examines the quality of population administration services and their contribution to improving overall public service performance. Using a descriptive qualitative approach, data were obtained through a literature review, observations, and an analysis of secondary documents related to public service standards in Indonesia. The analysis focuses on the five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy, as proposed in the SERVQUAL model.